Faktor-faktor yang mempengaruhi pengurusan bakat dalam sektor perbankan Islam di Alor Setar, Kedah - Tuan Noramy Shareena, Tuan Abdullah (2014)
The concept of talent management interests many researchers in the present. Talent management has been mostly practiced in every conventional financial institution in Malaysia. However, in the institutionalization of Islamic finance, talent management practices are considered rare and are still in the early stages. Talent management involves the process of attracting, developing, maintaining, and using the talent within the organization. This study aims to identify the factors that influence talent management in the Islamic banking sector. Talent management practices consist of various activities in different organizations that adopt talent management. In this study, researchers have used three activities or factors, career management, performance management, and learning and development. Samples were collected at 144 drawn from a population study involving 223 workers in the Islamic banking institutions in Alor Setar. The questionnaire used in the data collection process as a tool to prove the hypothesis. It is measured using seven-point Likert scale. Regression analysis was used to see the research results. The study found that career management is the most important factor influencing talent management in the Islamic banking institutions.